Predictors of mortality after atrial correction of transposition of the great arteries. Issue 23 (18th July 2022) - Antonová, Petra; Rohn, Vilem; Chaloupecky, Vaclav; Simkova, Iveta; Kaldararova, Monika; Zeman, Jan; Popelova, Jana; Havova, Mariia; Janousek, Jan
Abstract : Objectives: To determine the long-term and transplantation-free survival of all patients after atrial correction of transposition of the great arteries (TGA) in the Czech and Slovak republics, including its preoperative and perioperative determinants. Methods: Retrospective analysis of all 454 consecutive patients after atrial correction of TGA was performed. Of these, 126 (27.8%) were female, median age at operation was 7.4 months (Q1 5.3; Q3 13.3) and 164 (36.1%) underwent the Mustard procedure. The relationships between age, weight, the complexity of TGA, operative technique, additional surgical procedures, immediate postoperative presence of tricuspid regurgitation and revision procedures during follow-up to major composite outcome, as such defined as long-term and transplantation-free survival, were tested. Results: Early 30-day mortality did not differ between the Mustard (9.76%) and Senning (8.97%) cohorts (p=0.866). The long-term and transplantation-free survival, which differed between the Mustard and Senning cohorts in favour of the Senning procedure (HR 0.43; 95% CI 0.21 to 0.87), was shorter in complex TGA (HR 2.4; 95% CI 1.59 to 3.78) and in complex surgical interventions (HR 3.51; 95% CI 2.31 to 5.56). The immediate presence of at least moderate tricuspid regurgitation after correction was associated with a shorter long-term and transplantation-free survival in the univariate but not in the multivariable model. Conclusions: The lower long-term survival of patients after an atrial switch operation of TGA in the Czech and Slovak republics is associated with greater complexity of TGA, complex surgical interventions and application of the the Mustard operative procedure.